The Role of Trust in Political Corruption: Outline of the Subject - Turska-Kawa, Agnieszka (Political Preferences, 2015)
The article is an attempt to analyze the relations between political trust and one of the greatest problems of the public domain: political corruption. It seems obvious that corrupt behaviors revealed in the public space are supposed to undermine citizens' political trust. This thesis has been empirically verified many times. The author of the paper presents the cause and effect model with institutional trust as the independent variable. The article is an attempt to analyze the possible directions of its influence on political corrupt behaviors, assuming political trust to be the starting point, not the consequence, of the "social disease" occurring in the public domain. Key words: political corruption, political trust, political behaviors